Development of the competence in oral cancer early diagnosis during pre-professional training in Dentistry - Lisbeli Cantillo Acosta; Nuria Pérez Delgado; Isolina Vergara Vega; Nilvia Corral Verdecia (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: The increasing appearance of advanced oral cancer reveals the need of graduating professionals, prepared to contribute to its prevention and early diagnosis. Objective: To evaluate a system of teaching tasks for the development of competence in oral cancer early diagnosis. Methods: A pre-experiment was carried out with 32 students and 10 professors, who were involved in the teaching-learning process of the subject Comprehensive Dental Care for the Population of Dentistry degree in the University of Medical Sciences from Guantánamo, in the 2022-2023 academic year. For this purpose, the development of competence in oral cancer early diagnosis was determined as the variable, with its dimensions and indicators, and the significance of a system of teaching tasks for this objective was verified through the Wilcoxon test. Results: According to the Wilcoxon ranks, the teaching task system was reliable in contributing to the development of the competence under study (p<0.05). The students considered that this system is the ideal way for their training on the subject; in the same way, all teachers agreed regarding the relevance, feasibility, effectiveness, and practical utility of the teaching task system. Conclusions: The teaching task system applied during pre-professional practice of dentistry students proved to be feasible for the development of competence in oral cancer early diagnosis.